Edukasi Bahaya Laten Penyalahgunaan Narkoba pada Kalangan Pelajar SMA YPK Merauke, Provinsi Papua Selatan - Restu Monika Nia Betaubun; Rudini Hasyim Rado; Ilham Majid; Muh. Saiful Fahmi; Heldiaman Nduru; Ricky William Kocop (Pusat Riset dan Inovasi Nasional, 2024)
Students as a manifestation of the nation should be clear and kept away from things that can damage the future, including the dangers of drugs. This is realized because students are a group that is quite broad and easily influenced. The aim of this service is an educational outreach activity on the latent dangers of drug abuse among YPK Merauke High School students as a series of Legal Literacy Roadshows in 2023 to increase understanding and legal awareness about the bad effects of drugs. The method used is in the form of conveying information through socialization and leaflets/social media. The result of this service is increasing the knowledge of YPK Merauke High School students about the latent dangers of drugs and obtaining comprehensive drug prevention and control information.